The Role of Mushola Jabal Nur In Strengthening Aqidah Islamiyah and Mental Improvement Society - Imam Muhayat (Al-Hayat: Journal of Islamic Education, 2017)
All the builders, administrators, worshipers and Moslems in Jabal Nur Mosque are able to socialize and communicate to achieve the purpose of mushola with pilgrims, people, mosques, interfaith religion, community leaders, and related institutions, both internal and external in Jabal mosque Nur well. It is the main capital and as an entrance in aligning the heterogeneous phenomenon of life in the area of South Kuta.